Classification evaluation and distribution characteristics of sandstone interlayer reservoirs: A case study of the first member of Qingshankou Formation in Daqingzijing area, Changling Sag, Songliao Basin - XIAO Dianshi, GUO Xueyi, WANG Meng, XING Jilin, WANG Min, WANG Rui, ZHENG Lehua, GUAN Xiaodie (Youqicang pingjia yu kaifa)
The intercalated shale oil within the first member of the Qingshankou Formation in the southern Songliao Basin exhibits significant exploration potential, primarily influenced by the quality of its intercalations, which impacts both oil content and productivity. The physical properties of these interlayers are notably heterogeneous, highlighting the necessity to characterize and describe interlayer reservoirs comprehensively and establish a suitable classification scheme. This study utilized advanced techniques such as field emission scanning electron microscopy, high-pressure mercury injection, and nuclear magnetic resonance to characterize the reservoir. Employing the fractal theory associated with mercury injection, a physical property classification standard tailored for sandstone interlayers was developed. This standard was combined with logging data to predict the physical property parameters of the reservoirs, facilitating the identification and mapping of high-quality interlayer reservoirs. The results delineate the first member of the Qingshankou Formation in the Daqingzijing area into regions of varying source rock maturity: low maturity areas with a vitrinite reflectance（Ro） of less than 1.0% and areas with middle to high maturity source rocks（Ro greater than 1.0%）. It was found that interlayer physical properties deteriorate as the maturity of the source rock increases. A grading standard for interlayer physical properties was established, categorizing the sandstone interlayers into Class Ⅰ to Ⅲ, and deeming some as invalid reservoirs. From Class Ⅰ to invalid reservoirs, there is a sequential decrease in the content of large and medium pores, with reservoir space transitioning from intergranular pores and intergranular solution pores to intragranular solution pores and intergranular pores. The mercury injection profiles evolve from weak platforms and slow straight lines to convex shapes, indicating a gradual degradation in oil content. High-quality interlayer reservoirs are predominantly situated along the main body of the estuary bar and the underwater distributary channels, with the thickness decreasing from southwest to northeast. The findings of this research provide crucial insights for targeting interbedded shale oil prospects within the first member of the Qingshankou Formation in the southern Songliao Basin, assisting in the strategic selection of exploration and development sites.